Ultrasonographic fetal lung maturity profile: Fifteen years of experience in Hospital Nacional Arzobispo Loayza - Guibovich Mesinas, Alex Alberto (2015)
Objective: To evaluate the predictive capacity of Sonographic Fetal Lung Maturity Profile compared to the Clements test to reliably predict the Fetal Maturity, avoiding potential complications of amniocentesis, and constraints that exist in our environment for the use of markers prediction biochemical fetal maturity test as lecithin / sphingomyelin among others. Material and Methods: Descriptive, prospective study evaluating diagnostic parameters to determine fetal lung maturity using ultrasound and amniocentesis procedures, and comparing perinatal outcome as the gold standard. 1200 pregnant women hospitalized with high obstetric risk at Hospital Nacional Arzobispo Loayza from December 1995 to December 2010 were studied. They underwent sonographic profile of lung maturity with five parameters; liver, distal femoral epiphysis, and gestational age composed of multiple biometrics. All had an amniocentesis test to determine clement test in amniotic fluid (three tubes). If, by obstetric indication, pregnancy was ended within 48 hours of testing, perinatal outcome was evaluated. Results: 1251 newborns were studied, as there were 50 multiple pregnancies. The most common diagnosis was preeclampsia. Average gestational age by Capurro was 34.4 + 1.6 weeks (range 27-36 weeks), the weight of the newborns, in average, was 2136 + 580 gr (range 1050-2840 g). In total 80 newborns presented Hyaline Membrane Disease, diagnosed by clinical and radiological criteria. The prediction results for both sonographic fetal lung maturity and Clements test were: specificity (97.35%, 85.74%), sensitivity (86.25%, 75.0%), negative (69.0%, 26.43%) predictive value, positive predictive value (99.04%, 98.04%) respectively. Conclusion: Sonographic fetal lung maturity has a high predictive ability of fetal lung maturity, to be more specific and sensitive relative to Clements test, with the advantage of being easily repeatable and reproducible, it is noninvasive, fast, cheaper and can be done as an outpatient, predicting lung maturity better.